ANALISIS KEPUTUSAN INVESTASI DALAM MENINGKATKAN NILAI PERUSAHAAN PT.RADIANT ARTHA RAHARJA SEJAHTERA SEMARANG - Muchayatin Muchayatin; Shinta Mutia Dita (FEB UNTAG Semarang, 2018)
This study aims to determine investment decisions in increasing the value of the company contained in PT Radiant Artha Raharja Semarang. The method in this study uses qualitative study methods. Research on qualitative studies is a key instrument, data source sampling is done by snowbaal (sampling technique determined based on information). This research also uses source and technique analysis of transectional analysis.The results of this study state that investment decisions can increase the value of the company at PT Radiant Artha Raharja Semarang which can be seen based on the results of the financial statements in the period 2014 - 2016. In this study PT Radiant Artha Semarang's income increased in each year. Investment decisions are made by the company in 2015, seen from (net profit) in the year the report is minus (-) Rp. 19,235,171. This is because in 2015 PT Radiant Artha Sejahtera Semarang purchased the company's assets in the form of vehicles and building construction to open a new branch office.Keywords: Investment Decision, Company Value and PT Radiant Artha Raharja Semarang